ANALYSIS OF RISK ASSESSMENT TO IMPROVE OPERATIONAL BUSINESS PT MEIJI RUBBER INDONESIA (The Indonesian Journal of Business Administration, 2019)
PT Meiji Rubber Indonesia is a company engaged in the rubber manufacturing industry. This company is directly related to the automotive manufacturing industry market. The company has experienced a decline in performance as seen from the company's revenue which dropped by 19% for mold products and 8.3% for hose products from the target set for the 2018 projection. It is necessary to analyze management in the company by evaluating risks faced by the company. To evaluate this risk it is necessary to conduct an analysis of risk management and risk assessment to face the problem in operational process of the company.Weighting was carried out using the Analytic Hierarchy Process (AHP) method to calculate the weight of the pairwise comparison based on data obtained from respondents. With this method, risk weighting will produce a different level of risk from each risk factor. It can be determined the priority risk to be carried out with appropriate mitigation that can improve company performance. Based analysis results, there are 10 risk categories and 31 risk factors. Quality risk has a high level of importance according to respondents, namely 0.960. from the results of AHP weighting there are 9 risk factors with intolerable level.Keywords: Risk Assessment, Risk Evaluation, Analytic Hierarchy Process.